Health Counseling and Provision of Betel Leaves to Reduce Physiological Leucorrhea among Adolescent Girls: Penyuluhan Kesehatan dan Pemberian Daun Sirih untuk Mengurangi Keputihan Fisiologis pada Remaja Putri - Shinta Novelia; Bunga Tiara Carolin (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
In Indonesia, 75% of women have experienced vaginal discharge at least once, and half have experienced vaginal discharge twice or more. Vaginal discharge is a classic problem for most women. Ironically, most women do not know about vaginal discharge and the causes of vaginal discharge. If not handled properly, vaginal discharge can be fatal. Infertility and ectopic pregnancy (pregnancy outside the womb) can be one of the consequences of vaginal discharge. The early symptoms of uterine cancer usually start with vaginal discharge. This study's betel leaf (Piper betel Linn) belongs to the Peiperaceae family. The part used is the leaves. Betel leaf contains essential oils with compounds that have strong antibacterial properties, referred to as "kavikol" and "kavibetol". Anti-bacterial is also found in boiled betel in water. Betel leaf in traditional medicine is usually used for first aid in first-line treatment in daily medicine, especially as an antiseptic. This activity aims to increase young women's knowledge about the dangers of vaginal discharge and provide intervention in betel leaf boiled water to reduce physiological vaginal discharge. The activity results showed benefits for adolescents as evidenced by the decrease in the incidence of physiological vaginal discharge after being given counseling and betel leaf water.